The Effectiveness of Digital-Based Traditional Games in Improving The Ability to Solve Numeracy Story Problems for Elementary School Students - Ayu Tri Wahyuni; Lalan Soeharlan; Yuyun Dwi Haryanti (Eduvest - Journal of Universal Studies, 2026)
This study aimed to test the effectiveness of digital-based traditional games in improving third-grade elementary school students’ ability to solve numeracy story problems. This study used a quantitative approach with a quasi-experimental, nonequivalent control group design. The participants were 40 third-grade students from SD Sukarajawetan II, who were divided into an experimental group of 20 students who received numeracy instruction using digital-based traditional games and a control group of 20 students who received conventional instruction. Data were collected through pretest and posttest instruments consisting of 20 essay questions that measured students’ ability to understand the problem context, determine relevant operations, plan solution strategies, and perform calculations accurately. The data were analyzed using descriptive statistics, independent-samples and paired-samples *t*-tests, normalized gain (N-gain), and effect size (Cohen’s *d*). The results showed that both groups had equivalent initial abilities; however, the experimental group showed significantly greater improvement than the control group. The experimental group achieved a higher mean posttest score and a moderate N-gain, whereas the control group showed a lower N-gain category. The effect size analysis revealed a large practical impact of the intervention. These findings suggest that digital-based traditional games are more effective than conventional methods in improving students’ ability to solve numeracy story problems. The integration of local cultural games into the digital learning environment not only strengthens conceptual understanding but also increases student engagement and motivation in mathematics learning.